The Moderating Role of Executive Characteristics in the Effect of Transfer Pricing and Sales Growth on Tax Avoidance - Nadira, Siti; Febriani, Eka (Jurusan Akuntansi,Fakultas Bisnis dan Ekonomika,Universitas Surabaya, 2026)
Purpose – This study examines the effects of transfer pricing and sales growth on tax avoidance and investigates the moderating role of executive character in these relationships among companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. Methods – This study employs a quantitative research approach using secondary data obtained from annual reports and financial statements of publicly listed companies. The sample was selected using purposive sampling, resulting in 15 companies with 75 firm-year observations. Data were analyzed using multiple linear regression and Moderated Regression Analysis (MRA) with SPSS. Findings – The results indicate that transfer pricing has a significant positive effect on tax avoidance, suggesting that firms with higher levels of related-party transactions are more likely to engage in tax avoidance activities. Sales growth does not significantly affect tax avoidance, indicating that increasing sales performance does not necessarily encourage firms to adopt more aggressive tax planning strategies. Then, the findings reveal that executive character strengthens the positive relationship between transfer pricing and tax avoidance that risk-taking executives are more likely to utilize transfer pricing opportunities to reduce corporate tax burdens. However, executive character does not moderate the relationship between sales growth and tax avoidance. Implications – The findings contribute to the tax avoidance literature by highlighting the combined importance of organizational strategies and managerial characteristics in shaping corporate tax behavior. The study also provides practical insights for regulators in strengthening oversight of related-party transactions and encourages firms to maintain transparency and compliance when implementing transfer pricing policies. Furthermore, the findings emphasize the importance of considering executive risk preferences when evaluating corporate tax planning decisions. Originality - This study extends prior tax avoidance research by simultaneously examining transfer pricing and sales growth while incorporating executive character as a moderating variable. By integrating agency theory with executive risk-taking perspectives, the study provides a more comprehensive explanation of how managerial characteristics influence the effectiveness of transfer pricing strategies in facilitating tax avoidance within the Indonesian corporate context.